МЕТОДИКА РОЗРАХУНКУ ПРОТИЗАВАДНИХ ФІЛЬТРІВ DC/DC-ПЕРЕТВОРЮВАЧІВ ЗА ДОПОМОГОЮ ПРОГРАМИ LTspіc - Макаренко, В.В.; Пілінський, В.В.; Гурін, В.К. (Інститут електродинаміки НАН України, Київ, 2022)
The paper proposes a methodology for designing a filter for lowering conductive interference level, generated by pulse voltage converters. Not only the proposed method takes into account the requirements of the standard for electromagnetic compatibility, but also the parameters of the LISN node to measure the level of noise, which are given by a converter to a power supply chain. The articles describes the example of the filter design for a lowering DC-DC converter the noise level of which is in accordance with the standard CSPR25. All stages of design are illustrated by models, they are developed in the LTspice program. Models for analyzing the amplitude-frequency response of a interference filter loaded on a LISN are presented. It is shown that when modeling the operation of pulse sources, it is not advisable to use LISNs with the idealized characteristics of elements. The obtained filter calculations’ results confirm the correctness of the proposed method. References 11, figures 9.